PSXI-14 Effects of dietary neutral detergent fiber and starch ratio on performance and milk composition in lactating dairy cows: a meta-analysis. (7th December 2018) - Niu, J; Zhao, M; Bu, D; Zhang, Q; Zhang, W; Ma, L
Abstract: Carbohydrate is one of the major components in dairy cow's diet. Dietary carbohydrate can be divided into structural and non-structural fractions, within which neutral detergent fiber (NDF) and starch are the major components of the structural and non-structural carbohydrates. Meta-analysis was conducted to investigate the effect of dietary NDF and starch content on milk yield and composition in dairy cows in this study. 567 research papers retrieved from the Web of Science, Science Direct, PubMED and NCBI. The keywords include different combinations of dairy cows, milk production, milk composition, carbohydrate and forage to concentrate ratio. Through literature retrieval and data screening, 27 papers were collected including 119 experimental treatments. Data was analyzed using the MIXED model of SAS. Correlationship and meta regression analysis were performed comparing dietary NDF, starch and NDF:starch ratio on milk production and composition of milk component. Compared with dietary NDF and starch content, NDF:starch ratio was found to be highly correlated with DMI (rP2=-0.730, P2=0.664, P2=-0.788, PP=0.019), 1.36 kg (P=0.003), 0.06 kg (PPP=0.002) and 0.07 (P=0.007) unit, respectively. There was no significant meta regression relevance between dietary NDF:starch ratio and milk lactose content (P=0.893), milk fat yield (P=0.421). The meta-analysis results indicate that NDF:starch ratio could be used as a useful indicator for evaluating the dietary carbohydrates when formulating rations for dairy cattle. Key Words: